2020
DOI: 10.1038/s41392-019-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers in the diagnosis and prognosis of common leukemias

Abstract: The ability to identify a specific type of leukemia using minimally invasive biopsies holds great promise to improve the diagnosis, treatment selection, and prognosis prediction of patients. Using genome-wide methylation profiling and machine learning methods, we investigated the utility of CpG methylation status to differentiate blood from patients with acute lymphocytic leukemia (ALL) or acute myelogenous leukemia (AML) from normal blood. We established a CpG methylation panel that can distinguish ALL and AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Emerging studies have already shed light on a role for epigenetic dysregulation and classification in both ALL and AML. For example, methylation profiling of CpG sites can predict survival in each subtype [ 49 ], as well as can be used to distinguish lymphoid from myeloid cases [ 49 , 50 ]. We report here that, besides CpG methylation, global histone modification is also differentially expressed between lymphoid and myeloid leukemia and measurement at time of diagnosis correlates with response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have already shed light on a role for epigenetic dysregulation and classification in both ALL and AML. For example, methylation profiling of CpG sites can predict survival in each subtype [ 49 ], as well as can be used to distinguish lymphoid from myeloid cases [ 49 , 50 ]. We report here that, besides CpG methylation, global histone modification is also differentially expressed between lymphoid and myeloid leukemia and measurement at time of diagnosis correlates with response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo assays revealed that HIST2H2BF promotes malignant tumor behaviors in CRC. DNA methylation deregulation contributes markedly to tumor progression and acts as a vital marker to predict the response to therapy and prognosis in tumors (27,28). In our study, we examined the methylation levels of the HIST2H2BF promoter with methylation-specific PCR and bisulfite sequencing PCR in CRC tissues and adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have demonstrated epigenetic modifications act a critical role in AML through altering the transcriptional activation of oncogenes or tumor suppressors (6)(7)(8). DNA methylation is a common epigenetic modification in biological process and pathological processes in multiple tumors, such as regulation of tumorigenesis and development in breast cancer and lung cancer (9,10). Previous study has found that there is abnormal DNA methylation before cancer cell mutation (11).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting the expression of DNA methylation can effectively improve the effect of chemotherapy and prolong the survival time of AML patients ( 22 ). Previous studies have found that DNA methylation is a high sensitivity and specificity biomarker of AML in distinguishing it from other leukemia ( 9 ). Besides DNA methylation being strongly associated with prognosis of AML patients, it has been reported that different methylation types have different clinical outcomes for AML patients ( 23 ).…”
Section: Introductionmentioning
confidence: 99%